하바네로 고추 초산발효물의 품질 특성 및 생리활성 분석 - 박슬기(Seul-Ki Park); 조승화(Seung-Wha Jo); 임은정(Eun-Jung Yim); 강현진(Hyeon-Jin Kang); 최동성(Dong-Seong Choi); 정도연(Do-Youn Jeong) (한국식품과학회지, 2021)
Habanero red pepper (HRP)-fermented liquid with Acetobacter pasteurianus SRCM101474 was prepared, the quality characteristics measured and bioactivity analysis were measured. As the fermentation period increased, the number of viable cells increased, pH decreased, and acidity increased. After fermentation, the organic acid content of HRP was confirmed to be acetic acid with the highest content of 33413.54 ppm. Analysis of capsaicin and dihydrocapsaicin showed that the increase was significantly raised as acetic acid fermentation progressed. The total phenol and flavonoid contents as well as the antioxidant activity increased as the fermentation period passed. In addition, α-glucosidase inhibitory and pancreatic lipase inhibitory activities were significantly increased after fermentation. It was confirmed that it can be used as a functional material by measuring the physiological activities of antioxidant, anti-obesity, and anti-diabetes through fermentation, and the possibility of development as a spicy material and application product using it as capsaicin increases after fermentation. Acetobacter pasteurianus SRCM101474로 발효한 하바네로 고추 발효액을 제조하고, 품질분석 및 생리활성 분석을 측정하였다. 발효 기간이 증가함에 따라 생균수가 증가하였고, pH는 감소, 산도는 0.34%에서 3.18%로 증가하였다. 하바네로 고추 초산 발효물의 유기산 함량은 acetic acid, citric acid, succinic acid, oxalic acid 순으로 확인되었고, 발효 종료 시 acetic acid 함량이 33413.54 ppm으로 가장 높은 함량을 나타내었다. 매운맛 성분인 capsaicin과 dihydrocapsaicin 분석 결과 초산발효가 진행될수록 유의적으로 증가함을 보였다. 항산화 평가를 위해 총 페놀 및 플라보노이드 함량 및 DPPH, ABTS 라디칼 소거능을 측정한 결과 발효 기간이 지날수록 총 페놀함량 및 플라보노이드 함량이 증가하였고 항산화 활성도 유의적으로 증가하였다. 또한, α-glucosidase 억제 및 pancreatic lipase 억제 활성도 발효 후에 유의적으로 증가함을 보였다. 하바네로 고추의 초산 발효물의 항산화 활성 및 α-glucosidase, pancreatic lipase 억제 활성을 측정함으로써 기능성 소재로의 가능성을 확인하였고, 발효 후 capsaicin이 증가함에 따라 매운맛 소재 및 이를 활용한 응용제품으로서의 개발 가능성을 확인하였다.